2020
DOI: 10.3390/plants9060770
|View full text |Cite
|
Sign up to set email alerts
|

Geranium and Lemon Essential Oils and Their Active Compounds Downregulate Angiotensin-Converting Enzyme 2 (ACE2), a SARS-CoV-2 Spike Receptor-Binding Domain, in Epithelial Cells

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also known as coronavirus disease-2019 (COVID-19), is a pandemic disease that has been declared as modern history’s gravest health emergency worldwide. Until now, no precise treatment modality has been developed. The angiotensin-converting enzyme 2 (ACE2) receptor, a host cell receptor, has been found to play a crucial role in virus cell entry; therefore, ACE2 blockers can be a potential target for anti-viral intervention. In this study, we evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 27 publications
2
80
0
2
Order By: Relevance
“…1,8-Cineole is abundantly present in eucalyptus plants and is an effective treatment for pediculosis [ 15 ], as well as an efficient biological herbicide [ 16 ], antimicrobial, and antioxidant [ 17 ]. Recently, several essential oil-derived components, such as 1,8-cineole, have been reported to inhibit influenza symptoms [ 18 ] and severity of coronavirus disease 2019 (COVID-19) [ 19 , 20 , 21 ]. Furthermore, some researchers are also investigating using 1,8-cineole as a new treatment for COVID-19 symptoms [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,8-Cineole is abundantly present in eucalyptus plants and is an effective treatment for pediculosis [ 15 ], as well as an efficient biological herbicide [ 16 ], antimicrobial, and antioxidant [ 17 ]. Recently, several essential oil-derived components, such as 1,8-cineole, have been reported to inhibit influenza symptoms [ 18 ] and severity of coronavirus disease 2019 (COVID-19) [ 19 , 20 , 21 ]. Furthermore, some researchers are also investigating using 1,8-cineole as a new treatment for COVID-19 symptoms [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many natural compounds have been screened as therapeutic candidates for COVID-19 treatment through in silico molecular docking method [ 18 ]. Kumar et al reported that geranium, lemon oils, and the major compounds of lemon oils (citronellol and limonene) exhibited significant ACE2 inhibitory effects in epithelial cells [ 36 ]. Withanone, a compound from the alcoholic extract of Ashwagandha, could inhibit the mRNA expression of TMPRSS2 in MCF-7 cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no clinically used ACE2-based therapeutic agent; however, preclinical studies and clinical trials are continuing [ 25 , 317 , 332 ]. Several natural products , including flavonoids, e.g ., apigenin, quercetin, baicalin and epigallocatechin, and anthraquinones, e.g ., emodin (for a review [ 333 ]), and geranium and lemon essential oils [ 334 ] were reported to inhibit ACE2 activity in in vitro assays. Nicotianamine, isolated from soybean, was described to be a potent inhibitor of human ACE2 with an IC 50 of 84 nM [ 335 ].…”
Section: Pharmacology Of Ace2 and Ace2 Related Antiviral Treatmentsmentioning
confidence: 99%